A Whole Plant Analysis of Chloride and Sodium Exclusion Using a Range of Grapevine Rootstock Genotypes - R. R. Walker; D. H. Blackmore; J. D. Dunlevy; P. R. Clingeleffer; A. R. Walker (Australian Journal of Grape and Wine Research)
Background and Aims. Salt exclusion is an important attribute for wine grapes since many countries have limits to the concentration of sodium (Na+) and/or chloride (Cl−) tolerated in wine. The aim was to investigate whole plant capacity for Na+ and Cl‾ exclusion and the within-plant partitioning of accumulated ions to better understand these important salt tolerance traits. Methods and Results. Rooted cuttings of 140 Ruggeri and K51-40 (good and poor shoot Cl− excluders, respectively) and five hybrids from a cross between the two genotypes were used. When challenged with salinity, 140 Ruggeri limited the accumulation of Cl− and Na+ in the stem, petioles, and laminae and had a significantly lower whole plant concentration of Cl− and Na+ when compared to K51-40. The latter indicates that 140 Ruggeri accumulates less Cl− and Na+ than K51-40 by a lower uptake or a potentially greater efflux by roots, or both. While K51-40 accumulated significantly more Na+, it was able to retrieve it from the xylem; store it in the roots, stem, and petiole; and keep the lamina concentration comparable to that of 140 Ruggeri. Petioles of all genotypes appeared to play a role in limiting Cl− accumulation in laminae and particularly for K51-40, to limit Na+ accumulation in laminae. Conclusions. The grapevine capacity for Cl− and Na+ exclusion can be defined primarily as the lower net accumulation on a whole plant basis, reflecting the difference between the uptake and any efflux that may occur. Lower root to shoot transport is a key factor in shoot Cl− and Na+ exclusion. Petiole accumulation assists in limiting the Cl− and Na+ accumulation in the laminae. Significance of the Study. The study addressed the knowledge gap by examining Cl− and Na+ exclusion on a whole plant basis, highlighting a range of within-plant mechanisms that act in limiting the accumulation of both ions in the laminae.